Cognitive Development and Brain Gray Matter Susceptibility to Prenatal Adversities: Moderation by the Prefrontal Cortex Brain-Derived Neurotrophic Factor Gene Co-expression Network - de Mendonça Filho, Euclides José; Barth, Barbara; Bandeira, Denise Ruschel; de Lima, Randriely Merscher Sobreira; Arcego, Danusa Mar; Dalmaz, Carla; Pokhvisneva, Irina; Sassi, Roberto Britto; Hall, Geoffrey B. C.; Meaney, Michael J.; Silveira, Patricia Pelufo (Frontiers in Neuroscience, 2021)
Background: Previous studies focused on the relationship between prenatal conditions and neurodevelopmental outcomes later in life, but few have explored the interplay between gene co-expression networks and prenatal adversity conditions on cognitive development trajectories and gray matter density. Methods: We analyzed the moderation effects of a polygenic score for the Brain-derived Neurotrophic Factor gene network (BDNF ePGS) on prenatal adversity effects on child cognitive development. A score based on genes co-expressed with the pre-frontal cortex BDNF was created, using the effect size of the association between the individual SNP and gene expression (GTEx). Cognitive development trajectories of 157 young children from the Maternal Adversity, Vulnerability and Neurodevelopment (MAVAN) cohort were assessed longitudinally in 4-time points (6, 12, 18, and 36 months) using the Bayley-II mental scales. Results: Linear mixed-effects modeling indicated that BDNF ePGS moderates the effects of prenatal adversity on cognitive growth, with high BDNF ePGS been associated with higher susceptibility to environmental exposure. A parallel-Independent Component Analysis suggested that the relationships between single nucleotide polymorphisms (SNP)-based BDNF ePGS and gray matter density in areas involved in visual association processes (Brodmann area 19 and 18), and reallocation of attention and integration of information from across supramodal cortex (Brodmann area 10), differ in children exposed to prenatal adversity. Conclusions: Cognitive development trajectories and bra gray matter seem to be influenced by the interplay between prenatal environmental conditions and the expression of an important gene network (BDNF) that guides the growth and plasticity of neurons and synapses.